Biological monitoring of low level exposure to benzene in an oil refinery: Effect of modulating factors. (1st December 2018) - Carrieri, Mariella; Spatari, Giovanna; Tranfo, Giovanna; Sapienza, Daniela; Scapellato, Maria Luisa; Bartolucci, Giovanni Battista; Manno, Maurizio
Highlights: SPMA was confirmed as the best biomarker of benzene, even at very low levels of exposure. Cigarette smoking was confirmed as an important confounding factor for the benzene biomarkers. The GSTT1 but not GSTM1 genotype significantly modulates the urinary levels of SPMA. Toluene exposure, even at low concentrations, inhibits benzene metabolism to SPMA. Abstract: The aim of the study was to investigate the effect of various factors that modulate the metabolism of benzene, including smoking habits, metabolic genotype of GST and co-exposure to toluene, on the levels of three biomarkers, i.e. urinary benzene (UB), S-phenylmercapturic acid (SPMA) and t, t -muconic acid ( t, t -MA), in 146 refinery workers exposed to low levels of air benzene (AB) in the range <1.5–529.2 μg/m 3 (mean value 32.6 μg/m 3 ). The study confirmed the validity of SPMA as a good biomarker of benzene exposure even at low levels of exposure. It was also confirmed that cigarette smoking is the main confounding factor when assessing biological monitoring data of occupational exposure to AB. Our data indicate that the GSTT1, but not the GSTM1 genotype, significantly increases the urinary levels of SPMA, even at low levels of exposure. It is not known, though, whether subjects with a GSTT1 "null" genotype may be more susceptible to the effects of benzene. Finally, environmental toluene appears to inhibit the metabolism of benzene to SPMA even at low concentrations, also resulting in an underestimation by SPMA levels of the actual exposure of workers to benzene.